Pengaruh Komunikasi Dan Beban Kerja Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Pegawai Pada Kantor Dewan Perwakilan Rakyat Daerah Provinsi Sumatera Utara - Syaiful Bahri; Lailan Musfiroh Hasibuan; Sjahril Effendy Pasaribu (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The purpose of this study was to examine and analyze the influence of communication and workload on employee performance through job satisfaction at the Regional Representative Council Office of North Sumatra Province directly or indirectly. The approach used in this research is a causal approach. The population in this study were all state civil servants at the Regional Representative Council office of North Sumatra Province. The sample in this study used a sample of the Slovin formula totaling 52 state civil servants at the Regional Representative Council office of North Sumatra Province. Data collection techniques in this study used documentation, observation, and questionnaires. The data analysis technique in this study uses a quantitative approach using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Processing data in this study using the PLS (Partial Least Square) software program. The results of this study prove that directly communication, workload and job satisfaction have a significant effect on employee performance and indirectly communication and workload have a significant effect on employee performance through job satisfaction at the Regional Representative Council office of North Sumatra Province.